Whether drug detection in urine and oral fluid is similar? A systematic review. (20th April 2020) - Martini, Milena Binhame Albini; Batista, Thiago Beltrami Dias; Henn, Indiara Welter; Souza, Patrícia Tolentino da Rosa de; Vieira, Alexandre Rezende; Azevedo-Alanis, Luciana Reis
Abstract: Urine has been a biological matrix of choice for drug screening, but recent advances in technology and the introduction of commercial oral fluid assays have effectively established oral fluid as a viable alternative matrix. This systematic review aimed to evaluate the sensitivity of oral fluid in detecting some illicit drugs compared to urine, and to compare the initial and final detection times of these drugs in both fluids. The electronic search in MEDLINE, Cochrane Library, Scopus, and Web of Science was carried out covering studies published from January 2003 and June 2019, in order to find all valid studies that detected drugs in oral fluid and urine in the same patient. Studies about illicit drugs, such as tetrahydrocannabinol, cocaine, amphetamines and illicit opioids, with fluids collection at the same day, controlled drug administration during the study, reported administration interval and time of collection were favored. Out of 2598 studies identified by electronic search, 7 studies were selected for qualitative analysis. Five were clinical trials and 2 were crossover trials. In total, 74 patients aged 20–52 years underwent a diagnostic examination (4 studies with tetrahydrocannabinol, 1 with methamphetamine, and 2 with cocaine) after drug administration. Illicit drug detection in oral fluid is similar to urine but oral fluid has a strong potential for the immediate detection of recent marijuana use compared to urine. In relation to cocaine and methamphetamine, the largest drugs detection window is obtained through urine analysis. Oral fluids cannot replace urine for most of the purposes of drug testing.